DESCRIPTION OF EATING PATTERN IN PATIENTS WITH DIABETES MELLITUS AT IBNU SINA GRESIK HOSPITAL - Muhammad Syifaul Fikri; Susilo Harianto; Fanni Okviasanti (Universitas Airlangga, 2023)
Introduction: Poor dietary management is still commonly found in diabetes mellitus patients. Diet can be observed from the amount of food, type of food, and food schedule. The purpose of this research is to find out the diet of people with diabetes mellitus at the Ibnu Sina Gresik Hospital. Methods: This study was used a descriptive research design. The sample population in this study study were outpatient diabetes mellitus at Internal Medicine Polyclinic Ibnu Sina Gresik Hospital with the number 96 respondents. Sampling was taken using consecutive sampling who met the inclusion and exclusion criteria. Researchers collected data using dietary questionnaires. Univariate data analysis used is editing, coding, scoring, tabulation, and descriptive analysis. Results: This study was used a descriptive research design. The sample population in this study study were outpatient diabetes mellitus at Internal Medicine Polyclinic Ibnu Sina Gresik Hospital with the number 96 respondents. Sampling was taken using consecutive sampling who met the inclusion and exclusion criteria. Researchers collected data using dietary questionnaires. Univariate data analysis used is editing, coding, scoring, tabulation, and descriptive analysis. Conclusions: The diet off patients diabetes mellitus based on the amount of food is categorized as sufficient, based on the type of food categorized as bad, and based on the eating schedule is categorized as sufficient.